1985
DOI: 10.1073/pnas.82.16.5360
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the src gene product in inhibition of gap-junctional communication in NIH/3T3 cells.

Abstract: The effects of the src gene on the activity of protein kinase C and intercellular communication have been studied in transformed NIH/3T3 clones isolated from soft agar following transfection with the plasmid carrying the v-src gene (psrc-l1). Six transformed clones that were studied contained newly incorporated v-src genes in the genome, had an increased amount of pp6src, and showed enhanced activities of protein kinase C. Intercellular communication, studied by observing with autoradiography the transfer of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 35 publications
2
27
1
1
Order By: Relevance
“…This phenomenon is consistent with observations reported by others that pp60 ~''~ overexpression reduces cell-adhesion (Warren and Nelson, 1987) and cell-ceU communication (Azarnia et al, 1988). It is worthwhile to mention that pp60 ~-s' overexpression appears to mimic here the effect of pp60 "-~ since it has been reported that pp60 .... also impairs cell-cell communication (Chang et al, 1985;Crow et al, 1990). The presence of the long cellular processes filled with pp60 ~-~r~ in the NIH (pM c-src/focus)B cells plated at low density is also indicative of a lack of adhesive strength between these cells and the substratum.…”
Section: Localization Of Pp60 ~-'~ In Lnterphase C-src Overexpresser supporting
confidence: 81%
See 1 more Smart Citation
“…This phenomenon is consistent with observations reported by others that pp60 ~''~ overexpression reduces cell-adhesion (Warren and Nelson, 1987) and cell-ceU communication (Azarnia et al, 1988). It is worthwhile to mention that pp60 ~-s' overexpression appears to mimic here the effect of pp60 "-~ since it has been reported that pp60 .... also impairs cell-cell communication (Chang et al, 1985;Crow et al, 1990). The presence of the long cellular processes filled with pp60 ~-~r~ in the NIH (pM c-src/focus)B cells plated at low density is also indicative of a lack of adhesive strength between these cells and the substratum.…”
Section: Localization Of Pp60 ~-'~ In Lnterphase C-src Overexpresser supporting
confidence: 81%
“…It is interesting to note that the two proteins appear to exert here the same function in reducing intercellular adhesion and communication (Warren and Nelson, 1987;Azarnia et al, 1988;Chang et al, 1985;Crow et al, 1990).…”
Section: David-pfeuty and Nouvian-dooghe Localization Of The C-src Prmentioning
confidence: 99%
“…These results suggest that transformed NIH3T3 cells do not necessarily show lower levels of GJIC, which in turn, provides evidence that lower GJIC observed in NIH3T3 cells transfected with mutant 16 K proteins may not be a consequence of cell transformation. The results also con®rm our previous ®ndings that v-src induced NIH3T3 cell transformation is not associated with reduced GJIC ability (Bignami et al, 1988), which is at variance with other reports (Azarnia and Loewenstein, 1984;Chang et al, 1985). In order to examine whether GJIC modulation of NIH3T3 cells by mutated 16 K proteins was associated with changes in C643 expression, mRNA and protein levels of C643 were determined by RT ± PCR and Western blot analysis respectively.…”
Section: Gap Junctional Intercellular Communication In Nih3t3 Cells Tcontrasting
confidence: 52%
“…Earlier studies on the relationship between oncogenes and GJIC examined whether oncogenes can modulate GJIC. Such studies have shown that certain viral oncogenes such as the v-src gene can indeed inhibit GJIC (46)(47)(48). Other oncogenes have also been shown to inhibit GJIC.…”
Section: Gap Junctional Intercellular Communication and Oncogenesmentioning
confidence: 99%